Effect of B addition on the superelasticity in FeNiCoAlTa single crystals. (1st January 2021) - Czerny, M.; Cios, G.; Maziarz, W.; Chumlyakov, Y.I.; Schell, N.; Chulist, R.
Abstract: The study focuses on the superelastic effect in single-crystalline boron-doped Fe-based shape memory alloys. The homogenized and quenched single crystals were subjected to a heat treatment at 973 K for variable aging times. As a result, small and coherent nanometer-sized γ′ (Ni3 Al-type) precipitates were formed. It was established that Fe-28Ni-17Co-11.5Al-2.5Ta-0.05B single crystals oriented along [001] direction exhibit the fully reversible superelastic behavior up to 14.3% compression strain at 77 K reaching the maximum theoretical value. The boron addition suppressed completely the formation of the brittle β phase and reduced the average precipitate size of the γ′ precipitates. Using high-energy synchrotron radiation and high-resolution transmission electron microscopy analysis the volume fraction and precipitate size of γ′ were determined indicating that both factors are critical in obtaining the largest superelastic reversibility. Boron addition counters the initial effect of mechanical stabilization which was detected in single crystals without boron. Unlike the thermally induced martensitic transformation, applied stresses produce a different austenite/martensite interface composed of interchanging austenite and martensite variants. It is also demonstrated that upon loading/unloading cycles the moving transformation front divides the material into three district regions i.e. single variant of austenite, austenite intermixed with martensite and single variant of martensite. Graphical abstract: Unlabelled Image Highlights: Fe28Ni17Co11.5Al2.5Ta0.05B single crystals oriented along [001] exhibit fully reversible superelastic strain up to 14.3%. B addition suppressed the formation of brittle β phase and reduced the average precipitate size of γ′ to about 3–4 nm. Boron addition counters the initial effect of mechanical stabilization. A very different austenite/martensite interface as compared to thermally induced martensitic transformation was observed.